Development of electro-active forward osmosis membranes to remove phenolic compounds and reject salts. Issue 1 (25th November 2016) - Li, Jingguo; Liu, Qing; Liu, Yanbiao; Xie, Jianping
Abstract : A composite membrane that integrated forward osmosis with the electro-oxidation process was developed and achieved both effective removal of phenolic compounds (>92% at 2.5 V) and good salt rejection (>98%). Abstract : Forward osmosis (FO) is a promising membrane technology with good salt selectivity and high water permeability. However, it shows limited rejection of certain small organic molecules such as phenolic compounds. Here we developed a composite membrane resulting from the integration of FO with an electro-oxidation process to achieve both effective removal of phenolic compounds (>92% at 2.5 V) and good salt rejection (>98% for Na2 SO4 ). In addition, this composite membrane can be readily integrated into the currently used membrane system. The design presented in this study could provide an advanced solution to the critical demand for water and be used in the next generation of water treatment technologies.